Relationships between mitochondrial function and metabolic flexibility in type 2 diabetes mellitus. - Tineke van de Weijer; Lauren Marie Sparks; Esther Phielix; Ruth Carla Meex; Noud Antonius van Herpen; Matthijs Karel C Hesselink; Patrick Schrauwen; Vera Bettina Schrauwen-Hinderling (PLoS ONE, 2013)
INTRODUCTION: Mitochondrial dysfunction, lipid accumulation, insulin resistance and metabolic inflexibility have been implicated in the etiology of type 2 diabetes (T2D), yet their interrelationship remains speculative. We investigated these interrelationships in a group of T2D and obese normoglycemic control subjects. METHODS: 49 non-insulin dependent male T2D patients and 54 male control subjects were enrolled, and a hyperinsulinemic-euglycemic clamp and indirect calorimetry were performed. A muscle biopsy was taken and intramyocellular lipid (IMCL) was measured. In vivo mitochondrial function was measured by PCr recovery in 30 T2D patients and 31 control subjects. RESULTS: Fasting NEFA levels were significantly elevated in T2D patients compared with controls, but IMCL was not different. Mitochondrial function in T2D patients was compromised by 12.5% (p<0.01). Whole body glucose disposal (WGD) was higher at baseline and lower after insulin stimulation. Metabolic flexibility (ΔRER) was lower in the type 2 diabetic patients (0.050±0.033 vs. 0.093±0.050, p<0.01). Mitochondrial function was the sole predictor of basal respiratory exchange ratio (RER) (R(2) = 0.18, p<0.05); whereas WGD predicted both insulin-stimulated RER (R(2) = 0.29, p<0.001) and metabolic flexibility (R(2) = 0.40, p<0.001). CONCLUSIONS: These results indicate that defects in skeletal muscle in vivo mitochondrial function in type 2 diabetic patients are only reflected in basal substrate oxidation and highlight the importance of glucose disposal rate as a determinant of substrate utilization in response to insulin.